FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA DAN KETERSEDIAAN BERAS DI TINGKAT NASIONAL - Widodo Widodo (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
The  objectives  of  this  study  were:  (1)  to  understand  the  development  of domestic  rice  prices  at  the  national  level,  (2)  to  identify  factors  that  influence  the domestic rice prices at the national level, and (3) to determine the factors that affect the  availability  of  rice  at  the  national  level.  The  data  used  in  this  research  was secondary  data  obtained  from  the  BPS,  BULOG,  and  FAO  statistics.  The  data obtained were systematically recording in the form of a time series data since 1979 until 2008 at the national level. The model used in this research is simple regression equation or the Ordinary Least Square (OLS). This model was used to identify trends and  the  factors  affecting  the  price  and  availability  of  rice  nationwide. Regression equations  estimated  to  test  the  functionality  of  R2,  the  F-test,  t-test,  and  D-W.The results of this study indicate: (1) the rate of growth of retail rice prices at the national level has increased in the positive trend, (2) the domestic rice prices at the national level  is  influenced  by  the  base  price  of  grain  and  world  rice  prices,  and  (3)  the availability of long-term national from the year 1979-2008 rice prices was influenced by domestic supply, exchange rate farmers, the harvested area, and the availability of rice  before  and  after  the  moneter  crisis.  The  availability  of  rice  in  the  short  term before and after  the crisis were influenced significantly by harvested area, at the time of  pre-crisis  (1979-1997)  and  by  domestic  supply,  farmers  exchange  rate,  and  the harvested area, on the time after the crisis (1997-2008).